(untitled) (Neo Science Peer Reviewed Journal, 2023)
This scientific article explores the methods of syntactic analysis of works of art in elementary school textbooks. Artistic expressions, such as paintings, sculptures, and photographs, play a significant role in engaging students’ imagination and enhancing their understanding of various subjects. By incorporating syntactic analysis into the study of works of art, educators can help students develop critical thinking skills, aesthetic appreciation, and a deeper understanding of artistic elements. This article presents an overview of the importance of syntactic analysis in elementary education, examines various methods and techniques for analyzing works of art, and highlights the benefits of incorporating these methods into elementary school textbooks.